2018
DOI: 10.1177/0267659118763266
|View full text |Cite
|
Sign up to set email alerts
|

Routine CT scanning of patients retrieved to a tertiary centre on veno-venous extracorporeal membrane oxygenation: a retrospective risk benefit analysis

Abstract: Prospective studies should evaluate whether routine CT impacts outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…About 37% of the lesions were diagnosed from a CT scan performed in the absence of neurological symptoms. Low utilization of neuroimaging as a contributor to underreporting of ECMO-associated intracranial pathologies has been suggested in several previous studies 3,4,[17][18][19] . Thus, the incidence of BI in adult ECMO patients may be higher than previously estimated.…”
Section: Discussionmentioning
confidence: 93%
“…About 37% of the lesions were diagnosed from a CT scan performed in the absence of neurological symptoms. Low utilization of neuroimaging as a contributor to underreporting of ECMO-associated intracranial pathologies has been suggested in several previous studies 3,4,[17][18][19] . Thus, the incidence of BI in adult ECMO patients may be higher than previously estimated.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous experience has shown that computed tomography (CT) scanning is safe and feasible for patients on ECMO [19]. However, this data also showed that the effect of lung or abdominal scanning was modest on clinical decision-making.…”
Section: Imagingmentioning
confidence: 91%
“…It is likely that a routine total body CT is even less common. Two previous single-centre studies have reported the findings from routine use of whole-body CT but had substantially smaller sample sizes ( N = 65 [ 10 ], N = 198 [ 11 ]) with one cohort that did not routinely utilize intravenous contrast [ 11 ]. Several other single centre studies reported prevalence and clinical impact of CT imaging during treatment with V-V ECMO, but do not use a routine screening CT, have smaller sample sizes, and contain mixed adult and pediatric populations [ 17 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic CT has recognized diagnostic and prognostic yield in the management of patients with severe respiratory failure [ 8 , 9 ]. In contrast, the systematic use of an extrapulmonary screening CT in V-V ECMO patients is less common internationally despite data suggesting a high diagnostic yield [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%